#### Answer

$\sqrt{x-1}-1$

#### Work Step by Step

We are given: $f(x)=x-1,\ g(x)=\sqrt{x},\ h(x)=x-1$
We evaluate:
$(f\circ g\circ h)(x)=f(g(h(x)))=f(g(x-1))=f(\sqrt{x-1})=\sqrt{x-1}-1$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$\sqrt{x-1}-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.